Strategi Pengelolaan Hutan Kemasyarakatan Di Desa Keban Jati Kecamatan Air Nipis Kabupaten Bengkulu Selatan - Dwi Maryani; Reflis Reflis; Satria Putra Utama; Yenita Ekasari; Essy Anesta Asdami; Ranti Uchera (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2024)
This research aims to formulate a social forestry management strategy for HKm Sulian Besar in Keban Jati Village, Air Nipis District, South Bengkulu Regency. This research was carried out from July to August 2024 in Keban Jati Village, Air Nipis District, South Bengkulu Regency, Bengkulu Province. The research location was carried out in the Sulian Besar Community Forest. This research uses a combination method (mixed) dominantly qualitative and less dominantly quantitative. To recommend strategies for community forest management (HKm) that have achieved economic, social and ecological and institutional benefits by identifying using SWOT analysis to analyze various factors systematically. The position of the community forest management strategy in HKm Sulian Besar, Keban Jati Village, Air Nipis District, South Bengkulu Regency is in quadrant III, namely the turn around strategy where the implementation of the social forestry program of the community forest scheme has great opportunities but there are internal weaknesses so you have to choose the right strategy so that weaknesses are not reduce the odds. Alternative strategies that can be implemented include restructuring group institutions, increasing institutional, technical and marketing capacity, improving cultivation patterns and conducting effective NTFP marketing.